The Influence of Compensation, Work Environment, Work Motivation, Job Satisfaction, and Work Involvement on Employee Productivity in Restaurants in Tegal City - Tiara Diva Putriyanti; Erny Rachmawati; Suyoto; Hengky Widhiandono (LP2M IAIN Palopo, 2026)
The purpose of this study is to examine the effects of compensation, work environment, work motivation, job satisfaction, and work engagement on employee productivity in restaurants in Tegal City. This quantitative study employed a survey method involving 153 restaurant employees selected through purposive sampling. Data were collected using a structured questionnaire developed based on the indicators of each research variable. Data analysis was conducted using SPSS version 25, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that the five independent variables simultaneously have a significant effect on employee productivity (F = 128.521; Sig. < 0.001), with a coefficient of determination of 0.814, meaning that 81.4% of the variance in employee productivity is explained by the research model. Partially, compensation, work motivation, and work engagement have a positive and significant effect on employee productivity, while work environment and job satisfaction have a positive but insignificant effect. These findings emphasize the importance of integrated and sustainable human resource management in enhancing employee productivity in the restaurant sector